KEBERLANJUTAN USAHA MIKRO DAN KECIL BERBASIS SYARIAH DI ERA DIGITAL. STUDI KASUS: SYAR’I MART - Naufal, Muhammad Wildan; Ahmad Insan Kamil (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Sharia MSMEs are a type of business that is based on Islamic economic principles, with the aim of supporting economic and social growth ethically and in accordance with sharia. This research uses a qualitative approach with a literature review method. This method was chosen to analyze various concepts, theories and previous research findings related to the sustainability of sharia-based micro and small enterprises (MSEs) in the digital era. The results of this research state that with social media, a platform is created for customers to provide positive reviews regarding product quality and friendly service. This research shows that sharia MSMEs can be successful in the digital era by utilizing the right technology and marketing strategies. With a focus on halal products and services that comply with sharia principles.